Conditions for Encounters with Ultimacy Across Religious Boundaries - Konigsburg Joyce Ann (Open Theology, 2018)
Simply reading sacred texts across religious boundaries rarely achieves an “aha moment” or an encounter with ultimacy. The possibility of engaging with ultimacy requires establishing some necessary conditions. Any attempt to compel an experience results in false spiritual encounters rather than permitting authentic ones to occur. Therefore, a balance is necessary between being open to the possibility of a religious experience and seeking, but not forcing, an encounter with ultimacy. Placing oneself in a prayerful or spiritual state, for example, achieves the potential for encountering ultimacy by actively reading and meditating on various traditions’ sacred texts. These diverse writings relate others’ encounters with ultimacy and reveal multiple perspectives and imaginative descriptions of the transcendent. An encounter with ultimacy entails an open, willing, prayerful demeanor, intellectual curiosity, a rich imagination regarding divine imagery, and a sincere effort at understanding such a religious experience. A Christian contemplative process known as Lectio Divina satisfies many of these requirements. The method is general and flexible enough to utilize with sacred texts across religious boundaries; it invites a person to slow down, read, pay attention, respond with wonder, and humbly submit to the transforming presence and revelation of ultimate reality.